ANALYSIS OF THEORETICAL, SCIENTIFIC RESEARCH AND BEST PRACTICES OF BASKETBALL MANAGEMENT IN BULGARIA - Tsankov, Tsanko (Revista Inclusiones, 2020)
Management and development of basketball is a complex social and economic system. The objective of this study is to analyze some of the principle aspects of the management and development of basketball in Bulgaria through BFB. In this publication we have presented: theoretical and scientific research results from modern research studies and best practices in the management and development of basketball in Bulgaria and in other countries; European policy of sports management; design of a theoretical model for management of sports organizations and a sports federation; main areas of activity of the Bulgarian Basketball Federation (BFB). There are also recommendations for optimization of its functions and its contribution to basketball management in Bulgaria.